Influence of the pulsed AMF arc control on the vacuum arc and post arc characteristic in vacuum interrupters. (January 2018) - Ge, Guowei; Cheng, Xian; Liao, Minfu; Xue, Qinkuan; Zou, Jiyan
Abstract: The paper investigates the influence of the pulsed AMF arc control on the vacuum arc and the post arc characteristic to reveal the mechanism of AMF arc control in different control time and find the proper AMF arc control. The pulsed AMF control system is designed and the pulse width is adjusted from 1.5 ms to 10 ms by changing the capacitors. The test circuit is set up in the synthetic test circuit and the test vacuum interrupter (VI) is transparent in order to observe the development of the vacuum arc by the high speed CMOS camera. The rated voltage and current of the test VI is 10 kV and 25 kA respectively. The post arc current of the test VI is measured in order to analyze the post arc characteristic, such as the post arc charge, post arc conductance and dynamic dielectric strength. The development of vacuum arc and the post arc characteristic influenced by the pulse width, magnitude and control time of the pulsed AMF is obtained, which is useful to special magnetic contacts design. Highlights: The externally applied AMF system is designed and the pulse width can be adjusted from 1.5 ms to 10 ms while the magnitude of the AMF is adjusted from 0 to 200 mT. The test 10 kV/25 kA VI is transparent in order to obtain the vacuum arc photos by the high speed CMOS camera. The breaking test is conducted and the post arc current is measured. In addition, the maximum self-generated AMF of the cup typed VI is about 60 mT while the residual AMF in current zero is 10 mT. The post arc current and post arc charge with different AMF arc control is obtained. The AMF in the arcing time make the vacuum arc in diffuse mode and even distribution based on the vacuum arc photos, which is advantageous to decrease the post arc charge. However, the AMF near the current zero confined the arc plasma which restricts the diffusion of the arc plasma. There is an obvious influence of the AMF arc control on the vacuum arc development and the post arc charge. According to the test result of the pulsed AMF OF 2.5 ms, the optimal or effective AMF is in the arcing time just before the column arc mode. The residual magnetic field should be as small as possible by optimal design of the contacts. The paper supplies some reference for the special magnetic contacts design.